2007
DOI: 10.1583/06-2045.1
|View full text |Cite
|
Sign up to set email alerts
|

Retrievability of the Günther Tulip Vena Cava Filter after Dwell Times Longer Than 180 days in Patients With Multiple Trauma

Abstract: If retrieval of a Gunther Tulip filter with an dwell time >180 days is considered, the patient should be ambulatory and a candidate for anticoagulation if indicated; notably, the filter should have a <25 degrees tilt. Under these circumstances, retrieval of the Günther Tulip filter after 180 days of dwell time appears justified and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 16 publications
2
22
1
1
Order By: Relevance
“…The longest published implantation time prior to successful removal that we were able to identify for the Recovery filter is 735 days [18], although anecdotal reports of longer implantation to retrieval times have been made to the manufacturer, up to 975 days (Janet Hudnall, senior marketing manager for IVC filters, Bard Peripheral Vascular, personal communication). Prolonged retrieval times have also been reported for the Gunther Tulip filter (Cook) [12], although the longest we have found in the literature is only 475 days [24]. Although the Recovery filter is no longer available, we believe that the revised G2 filter should similarly allow for long retrieval intervals.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The longest published implantation time prior to successful removal that we were able to identify for the Recovery filter is 735 days [18], although anecdotal reports of longer implantation to retrieval times have been made to the manufacturer, up to 975 days (Janet Hudnall, senior marketing manager for IVC filters, Bard Peripheral Vascular, personal communication). Prolonged retrieval times have also been reported for the Gunther Tulip filter (Cook) [12], although the longest we have found in the literature is only 475 days [24]. Although the Recovery filter is no longer available, we believe that the revised G2 filter should similarly allow for long retrieval intervals.…”
Section: Discussionmentioning
confidence: 53%
“…With these filters, they may be used as a permanent device or they have the option to be retrieved percutaneously within a period which may be defined by the manufacturer. Retrieval after extended implantation periods (greater than 180 days) has also been reported [11,12].…”
Section: Discussionmentioning
confidence: 88%
“…Current evidence showed that delayed filter retrieval was feasible, with a recent series reporting a mean filter dwell time of 143 days and successful retrieval achieved as late as 6.5 years after filter placement. 25,26 Second, a standardized system should be in place to follow-up patients with IVC filter. Before filter insertion, its indication and anticipated placement duration should be clearly documented.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that retrieval Gunther tulip IVCF could be placed for permanent use. 10,11 All patients received the regular use of a pneumatic foot tourniquet together with the administration of anticoagulants, according to the guidelines of The University of Tokyo Hospital. Their hospital records were retrospectively reviewed, in particular the data associated with IVCF placement.…”
Section: Methodsmentioning
confidence: 99%